Pengembangan Keterampilan Berpikir Kritis: Manajemen Model Pembelajaran Terintegrasi di Sekolah Menengah Kejuruan Swasta Teladan Pematangsiantar - Putri Elisabet Marpaung; Lasio Loy Della Simanjuntak; Monica Evelina Silaban; Meta Mei Isa Haloho; Bahtiar Sihaloho; Benjamin Albert Simamora (Young Journal of Social Sciences and Humanities, 2026)
Vocational High Schools (SMK) are not only required to produce work-ready graduates but also to equip them with 21st-century soft skills grounded in critical thinking as the primary capital for navigating the dynamics of the world of work. This article aims to examine learning management in developing the critical thinking abilities of SMK students to enhance their competitiveness in the employment sector. The study employs a descriptive qualitative approach, with primary data sources consisting of teachers, students, and the school principal, collected through observation, in-depth interviews, and structured documentation. The findings reveal that the developed learning management focuses on integrating various learning models as a systemic strategy to foster students’ critical thinking abilities. This integration is reinforced by teachers’ roles in implementing problem-based learning, project-based learning, guided inquiry, and cooperative learning, which consistently encourage students to think analytically, reflectively, and solution-oriented. This paper proposes that strengthening learning management serves as a key strategy in shaping SMK graduates who are not only professionally competent but also adaptive, reflective, and ready to compete in an increasingly complex and competitive world of work.